ANALISIS PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR PESERTA DIDIK PADA MATERI AKU DAN LINGKUNGAN SEKITAR DI KELAS III SD NEGERI 2 KARANG ANYAR - Situmorang, Hotmian; Mufti Riyani; Alpidsyah Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of the surrounding environment as a learning resource for the topic "Me and the Surrounding Environment" in the third-grade class at SD Negeri 2 Karang Anyar, as well as to identify the obstacles encountered and the teachers' efforts in implementing this approach. The study employs a descriptive qualitative approach, involving teachers, students, and the school principal as subjects. Data were collected through observation, interviews, and documentation. The results indicate that the school environment is utilized as a learning resource through the use of real objects—such as leaves, trees, plants, soil, stones, the schoolyard, the garden, and the school building—alongside activities involving observation, discussion, note-taking, and presentations. This utilization aligns with the characteristics of the IPAS (Natural and Social Sciences) curriculum regarding the environment and enables students to gain direct learning experiences. Obstacles identified include student distractibility, limited facilities and tools, time constraints, and weather or environmental conditions. Teachers' efforts to address these challenges include providing guidance and support, utilizing available tools and materials, managing time effectively, and adapting activities to environmental conditions. The findings demonstrate that the school environment serves as both a learning resource and a learning venue, integrating real objects, student activities, and the teacher's role as a facilitator.